2021
DOI: 10.7759/cureus.14738
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Vitamin D and Zinc Levels With Alopecia Areata Phenotypes at a Tertiary Care Center

Abstract: Alopecia areata (AA) is a common immune-mediated hair disorder that presents in different clinical patterns. This study aims to find the association between vitamin D and zinc levels with AA phenotypes, to determine the common comorbidities in AA patients, and to assess the influence of age, gender, and body mass index (BMI) on AA phenotypes. MethodsThis is a cross-sectional study conducted at King Abdulaziz Medical City (KAMC) in Jeddah, Saudi Arabia. Data were collected through retrospective chart review of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…[ 46 ] in Saudi patients reported that hypothyroidism was the most common medical comorbidity in patients with AA, followed by atopic diseases, diabetes, and mood disorders. Most of these comorbidities were identified in patients with a patchy type of AA [ 46 ]. Similar results were reported by Alshahrani et al.…”
Section: Resultsmentioning
confidence: 99%
“…[ 46 ] in Saudi patients reported that hypothyroidism was the most common medical comorbidity in patients with AA, followed by atopic diseases, diabetes, and mood disorders. Most of these comorbidities were identified in patients with a patchy type of AA [ 46 ]. Similar results were reported by Alshahrani et al.…”
Section: Resultsmentioning
confidence: 99%
“…In 2022, Sule Goksin et al reported that AA patients not only tend to have autoimmune diseases but also develop multiple systemic diseases, autoimmune diseases, and psychiatric disorders [82]. Moreover, a study conducted in Saudi Arabia found that 62.7% of the 177 AA patients they recruited had insufficient serum vitamin D levels [83], which can also be observed in pediatric alopecia areata. A cross-sectional study found that pediatric alopecia areata patients tend to have comorbidities including atopic dermatitis, anemia, obesity, psoriasis, and depression.…”
Section: Disease Associations With Aamentioning
confidence: 99%
“…Vitiligo is a common depigmenting disorder affecting the skin and hair with 0.1%-2% incidence rate. 50,51 The cause appears to be a loss of functional melanocytes. It is generally agreed that there is an absence of functional melanocytes as result of autoimmune destruction.…”
Section: Vitiligomentioning
confidence: 99%
“…[61][62][63] Four involved mechanisms include follicular proliferation with ruptures, sebum production, inflammation, and the presence of Cutibacterium acnes which induces inflammation. 50,64 In the last five years eight studies were identified that measured serum d zinc level in patients with acne. Data are conflicting as five of these studies concluded significant differences in serum zinc levels between acne and control groups.…”
Section: Acne Vulgarismentioning
confidence: 99%
See 1 more Smart Citation